Rural-Urban differentials in the factors associated with modern contraceptive usage among married reproductive-aged women in Hubei province, China - Joseph Lasong; Min Li; Yula Salifu; Torjim Salifu; Huiping Zhang; Kai Zhao; Yun Zhao (BMC Public Health)
Abstract Background China’s fast development is markedly impacting on migration, which has brought tremendous pressure and severe challenges to family planning services. Moreover, family planning (FP) is mostly regarded as women’s responsibility by some Chinese cultures and societies. Several female contraceptives are easily accessible but only a few are known and widely used. Therefore, this study examined the rural-urban differentials in the factors associated with modern contraceptive usage among married non-pregnant reproductive-aged Chinese women in Hubei Province. Methods A community-based cross-sectional study was conducted from 1st January 2014 to 30th November 2016 to recruit 6,356 married reproductive-aged women in Hubei Province, China. Descriptive statistics, chi-square tests, and multivariable logistic regression were used to examine associations between sociodemographic and reproductive health factors and contraceptive use. Statistical significance was set at p ≤ 0.05. Results The study showed that unweighted proportion of contraceptive use among rural and urban reproductive aged women were 88.5% and 87.1% respectively. Usage of contraceptive was found to be predicted by age (< 25 years: AOR = 3.14, p = 0.001; 25 to 34 years: AOR = 2.00, p = 0.018), ethnic minority other than Han (AOR = 0.29, p = 0.001), number of children (no child: AOR = 12.55, p = 0.001; one child: AOR = 1.75, p = 0.002), and knowledge of condom (AOR = 3.19, p = 0.001) among rural dwellers. Age (< 25 years: AOR = 2.82, p = 0.005), number of children (no child: AOR = 10.68, p = 0.001), spouse use of contraceptives (AOR = 1.63, p = 0.001) and discussion on contraception with spouse (AOR = 1.79, p = 0.003) were determinants of contraceptive usage among urban dwellers. Conclusions Contraceptive use across both residencies were high. Age, ethnic minority other than Han, parity, and knowledge of condoms were factors associated with contraceptive use among rural settlers. Also, age, parity, spousal usage of contraceptives and discussion on contraception with spouses were determinants of contraceptive use among urban settlers. Thus, family planning education should be all-inclusive, well prepared, and relevant to women to allow them to make informed decisions and improve the uptake of family planning services among rural residents. Men should be encouraged to participate in reproductive health service counselling and support to improve comfort and uptake of contraceptives among female spouses among urban populations.